Evaluation of children's pain expression and behavior using audio visual distraction. Issue 5 (23rd February 2021) - Delgado, Alicia; Ok, Soo‐Min; Ho, Donald; Lynd, Tyler; Cheon, Kyounga
Abstract: Objectives: Dental anxiety distresses children and their families with consequent poor oral health and costly pediatric dental services. Children's behaviors could be modified using a distraction technique for improved dental treatment. The study evaluates the effects of an audio‐visual distraction on children's behaviors and pain expressions during dental treatment. Material and Methods: One hundred healthy children, between 4 and 6 years of age, were randomly assigned to one of two groups: audio visual distraction (AVD, N = 61) group and control (CTR, N = 39) group. The pre and post pain expression was collected using a faces pain rating scale from the participated children. Children's behavior was evaluated using the Frankl behavior rating scale by the assigned dentist. Data was analyzed using chi‐squared tests and analysis of variance. Results: The AVD group demonstrated more "definitely positive" behavior (91.8%) compared to the CTR group (35.9%) based on the Frankl scale evaluation from pre‐ and post‐treatment ( p < 0.0001). The pain rating scale did not demonstrate a significant difference in post‐treatment pain scales ( p = 0.2073) or changes in pain ( p = 0.1532) between the AVD group and CTR group. Conclusions: The AVD is an effective distraction tool for young children during dental treatment regardless of child's subjective pain expression.